Osteoarthritis induced by monosodium iodoacetate model: evolution of inflammatory, nociceptive and histopathological markers - da Silva Nascimento, Francisco Glerison; Fernandes Oliveira Marques, Gabriela; Sampaio Cavalcante, Adriane; Feitosa Holanda, Bianca; Lima Mota, Mário Rogério; de Freitas Pires, Alana; Ribeiro Castro, Rondinelle (Journal of Health & Biological Sciences, 2024)
Objectives: this study aimed to highlight the evolution of the osteoarthritis (OA) model induced by monosodium iodoacetate (MIA) and its collaboration with the knowledge of the pathophysiology of inflammation, hypernociception and cartilage degeneration. Methods: PubMed and Science Direct were used with the descriptors: knee osteoarthritis or osteoarthritis of ankle) and (rat or osteoarthritis induced by monoiodoacetate) and (animal model of osteoarthritis or joint nociception). Studies containing rats, mice, and monoiodoacetate-induced osteoathritis were included. Exclusion criteria were: Animal models of osteoarthritis induced by destabilization; meniscectomy-induced osteoarthritis; non-invasive animal models of osteoarthritis induced by fracture, compression and tibial overload; animal models of osteoarthritis with large animals and models of osteoarthritis by papain or bacterial collagenase. We summarized studies that used MIA to induce knee or ankle OA in rats or mice and the evolution of the inflammatory markers. Results: a total of 38 original manuscripts met the inclusion criteria and were considered in the study. The model of OA induced by MIA is well-established and explored with several methodologies and has been widely used in different species. MIA induces cell death, progressive loss of chondrocytes and histological changes that mimics human OA. Studies with this model demonstrated inflammation, neurogenic hyperalgesia, release of cytokines and matrix metalloproteinases. More recently, molecular biology data confirm the activation of nuclear transcription factors, which modulates the expression of citokines in apoptotic chondrocytes. Conclusion: the MIA-induced OA has been useful in predicting several characteristics for the elucidation of osteoarthritis pathophysiology.